Effects of dietary Chlorella ellipsoidea on growth performance, body composition, and hematology of stinging catfish, Heteropneustes fossilis - Alam Asraful; Bristy Fouzia Sultana; Amzad Hossain M.; Rabiul Islam M.; Fatema Umme Kaniz; Golam Rasul M. (Fisheries & Aquatic Life)
Microalgae have emerged as a promising feed supplement in aquaculture diets. Therefore, the aim of this study was to investigate the effect of Chlorella ellipsoidea as a feed supplement on the growth performance, body composition, and hematology of stinging catfish, Heteropneustes fossilis (Bloch). Five experimental diets were formulated to conduct this experiment by supplementing 0, 2.5, 5.0, 7.5, and 10% C. ellipsoidea at the expense of fish meal, and these are referred to as the control, CE 2.5, CE 5, CE 7.5, and CE 10 diets, respectively. A total of 900 fish (mean body weight of 0.50 ± 0.01 g) were divided equally into15 glass aquaria (180 L). Triplicate groups of fish were fed with each experimental diet to satiation twice daily for 10 weeks. At the end of the feeding trial, the weight gain (%) of the fish fed CE 5 and CE 7.5 was significantly (P < 0.05) higher than that of fish fed the control diet. The specific growth rate (SGR) of the fish fed CE 5 was significantly higher (p < 0.05) but comparable to those fed CE 2.5 and CE 7.5. The feed conversion ratio (FCR) of the fish fed CE 5, CE 7.5, and CE 10 was significantly (P < 0.05) lower, and the protein efficiency ratio (PER) of the fish fed CE 7.5 and CE 10 was significantly (P < 0.05) higher compared to all the other diets. In comparison to the control, dietary C. ellipsoidea of 5.0–10.0% significantly (P < 0.05) increased the protein content of stinging catfish, while lowering the lipid and moisture contents. The red blood cells, white blood cells, hemoglobin, hematocrit, and mean corpuscular hemoglobin levels of H. fossilis increased significantly (P < 0.05) when the fish were fed 5.0–10.0% dietary C. ellipsoidea compared with the control. Based on the findings of the study, 5.0–10.0% C. ellipsoidea supplementation was optimal in the stinging catfish diet to improve growth performance, body composition, hematology, and immunological response. However, based on regression analysis, the optimum level of C. ellipsoidea as a feed supplement was calculated to be 4.9–5% in stinging catfish.